An ecological settlement design for refugees in Kocaeli - Küçük, Merve; Karadayi, Tülay Tikansak (Research and Development Academy, 2020)
After the civil war in Syria, many refugees sought refuge to Turkey. It brought along many environmental problems such as sudden population growth and resource shortage. It is thought to design an ecological settlement that can produce its own energy and be self-sufficient as a solution due to the limited natural resources, in order to meet the need for shelter quickly in emergency situations. With this in mind, in order to create an ecological settlement, a sample and literature search was conducted and sustainable ecological settlement criteria were determined. As a place operation, the position is preferred in Turkey and that provides employment and by day increasing the number of refugees residing Kocaeli been selected. In line with the ecological settlement criteria, a survey was conducted to understand the accommodation problems and environmental awareness of Syrian refugees living in Kocaeli. Ecological living units are designed in line with the environmental, climatic and sociological data obtained. The units are placed in accordance with the physical environmental conditions of the plot chosen for ecological settlement. In the conclusion part, the applicability of the designed project has been evaluated in line with economic, sociological and ecological criteria and its positive and negative aspects have been discussed. In the sample area selected in this study, it is aimed to create an ecological residential area that provides energy, water and raw material conservation in accordance with environmental data, protects the ecosystem, and provides adequate comfort conditions for the users indoors. This study is intended to be a source for ecological settlement projects in order to create livelihoods for low-income groups and to stimulate agriculture, except in emergencies. © 2022 Elsevier B.V., All rights reserved.
Keywords: Ecological living unit; Ecological settlement; Ecology; Kocaeli/Turkey; Refugee